Attitudes to Employment of Professionally Qualified Refugees in the United Kingdom. (28th January 2013) - Willott, John; Stevenson, Jacqueline
Abstract: This paper explores the attitudes to work and experiences seeking employment of professionally qualified refugees enrolled on a course to enhance their employability skills in Leeds, United Kingdom (UK). We analyse the results within the framework of conceptual models describing the transition of refugees into employment (which are essentially linear) and those that categorize refugees according to their resettlement styles based on their social features and the host society's response. Our data reinforce that these people are (initially at least) highly motivated to work, strongly identify with their profession and suffer considerable loss of self‐esteem as they are unable to secure appropriate employment. Attitudes to securing employment were often related to their length of time in the UK. Recent arrivals were more positive about returning to their profession, even if this meant retraining, developing skills and time spent in alternative employment. Many of those here for longer were resigned to retraining, and the worst cases felt despair and feelings of betrayal. Our work showed that many had poor job search strategies and a lack of knowledge of the culture and norms of their chosen profession. We argue that the generic support of statutory employment services or the voluntary sector is inappropriate and that there is a role for professional bodies to be more active in their engagement with these groups of people. The results suggest that conceptual models need to be more nuanced to capture the experiences of these refugees: attitudes to work can cycle from optimism to disillusionment, so a linear model will not capture the full complexity, and we also found evidence of shifting among categories of resettlement styles.